BONSAI BERINGIN DAN SERUT SEBAGAI ALTERNATIF PENDAPATAN PETANI MILENIAL DI MASA PANDEMI COVID 19: BONSAI BERINGIN DAN SERUT ALTERNATIF PENDAPATAN PETANI MILENIAL - oryza sativa, rima dewi; Dita Serdani, Army (Universitas Islam Balitar, 2022)
Bonsai is a plant that is easy to care for and does not require extra care or attention. A little sun and a little water are needed to maintain a bonsai. It is from this wealth that the art of bonsai in Indonesia was born (Najoan et al, 2015). The art of maintaining and shaping this dwarf plant called